Collaborative Governance and Infrastructure Development in Indonesia: A Review - Dwi Agus Prastiyo (Brawijaya University, 2019)
Collaboration in public sector are a common concept. Its implementation are solely used to tackle the problem in public sector issues which often require all stakeholder to participate in oreder to achieve common goal without endanger every other stakeholder goals, and also to efficiently handle the issues that can only be solved by merge all resources from every stakeholder in the matter. In infrastructure development in Indonesia, often the issues are regarding the split allocation resource and authority that possessed by every stakeholder. This often worsen the development and need the approach of collaboration in which offered by collaborative governance in general. In the attempt to improve the infrastructure development in Indonesia, collaborative governance might be the best solution as of now if we investigate the general concept of collaborative governance and the state of the issue of infrastructure development in Indonesia.Â